Changing Families, Changing Food
XV, 292 p.
Keywords: Approaching family through the lens of food, this book provides a new perspective on the diversity of contemporary family life, challenging received ideas about the decline of the family meal, the individualization of food choice and the relationship between professional advice on healthy eating and the everyday practices of 'doing family'.